MiR‐320a regulates high mobility group box 1 expression and inhibits invasion and metastasis in hepatocellular carcinoma. (11th April 2017) - Lv, Guixiang; Wu, Mingjuan; Wang, Meijie; Jiang, Xiaochen; Du, Jingli; Zhang, Kaili; Li, Dongliang; Ma, Ning; Peng, Yahui; Wang, Lujing; Zhou, Lingyun; Zhao, Weiming; et al.
Abstract: Background & Aims: Several studies have shown that miR‐320a induces apoptosis, inhibits cell proliferation, and affects cell cycle progression as a tumour suppressor in many cancers. However, the involvement of miR‐320a in the invasion and metastasis of hepatocellular carcinoma (HCC) is still unknown. Methods: Endogenous miR‐320a and high mobility group box 1 (HMGB1) expressions were assayed by real‐time PCR. Luciferase activities were measured using a dual‐luciferase reporter assay system. Western blots were used to determine the protein expressions of HMGB1, MMP2, and MMP9. Invasion and metastasis of tumour cells were, respectively, evaluated by the transwell invasion assay and the wound healing assay. Results: The expression of miR‐320a was significantly decreased in 24 of 32 (75%) HCC tissues and associated with the invasion and metastasis of HCC. Furthermore, we demonstrated that HMGB1 was a direct target of miR‐320a and there was a significant negative correlation between miR‐320a and HMGB1 expression in HCC. Ectopic expression or inhibition of miR‐320a potently regulated the invasion and metastasis of HCC cells in HMGB1‐dependent manner. Conclusions: Our results showed that miR‐320a was involved in the invasion and metastasis by targeting HMGB1 and had an anti‐metastasis effect in HCC.